GENUS RHOGOGASTER KONOW WITH A NEW SPECIES FROM ORIENTAL REGION (HYMENOPTERA : TENTHREDINIDAE) - BHAIRT, HIMIENDER; SAINI, M.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Genus Rhogogaster is reported first time from Oriental region. A species Rhogogaster indica Konow n. sp. has been described and illustrated. The relevant data is also provided.